2009
DOI: 10.1213/ane.0b013e31819b03d8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Low-Dose Remifentanil on Responses to the Endotracheal Tube During Emergence from General Anesthesia

Abstract: Low-dose remifentanil during emergence did not prolong wake-up but reduced the incidence and severity of coughing from the endotracheal tube.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 7 publications
1
79
1
Order By: Relevance
“…Anatomical and physiological changes contribute to a situation that can be more challenging than intubation for the anesthesiologist. A severe extubation response can significantly increase BP and HR (Aouad et al, 2009), potentially leading to postoperative hemorrhage, intracranial hypertension and/or intraocular hypertension (Leech et al, 1974;Saghaei et al, 2005;Irwin, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical and physiological changes contribute to a situation that can be more challenging than intubation for the anesthesiologist. A severe extubation response can significantly increase BP and HR (Aouad et al, 2009), potentially leading to postoperative hemorrhage, intracranial hypertension and/or intraocular hypertension (Leech et al, 1974;Saghaei et al, 2005;Irwin, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Maintenance of a low-dose remifentanil infusion has been reported to decrease the incidence of coughing and induce a smooth emergence from general anesthesia. 3 Several studies have shown that the optimal effect-site concentration (Ce) of remifentanil for cough suppression during emergence ranges from 1.5-2.9 lgÁmL -1 . [4][5][6][7] Further increasing the dose of remifentanil can be effective in preventing coughing but may cause respiratory depression, delay emergence from anesthesia, and increase the incidence of postoperative nausea and vomiting.…”
mentioning
confidence: 99%
“…2 Other newer exciting strategies described in recent literature include the use of dexmedetomidine, the use of low-dose remifentanil to ameliorate endotracheal tubeinduced airway irritation during emergence, 4 and the use of the Boussignac CPAP system immediately following extubation to improve oxygenation. 5 The OSA patient poses special challenges to the anesthesiologist.…”
Section: Replymentioning
confidence: 99%